The MAO NASU Plate Archive: "observations in the past" of minor planets - Sergeeva, T.P.; Golovnya, V.V.; Sergeev, A.V. (Кинематика и физика небесных тел, 2005)
The Plate Archive of the Main Astronomical Observatory of the National Academy of Sciences of Ukraine (MAO NASU) includes 20 thousands of direct sky area plates, which have been taken for various astronomical projects during the period of about 50 years. Those plates contain more then hundred thousand images of minor planets with magnitude up to 16.7m. About 10% of minor planets, which may be found on our archive plates were firstly discovered after the time when plates have been taken. So, we can rediscovery them due to the so-called “observations in the past”. In the paper the criteria for choose of objects and methods of their search, identification, and determination of their position are discussed. First results of the search for potentially hazardous asteroids in the MAO plate archive are presented.